2021
DOI: 10.31219/osf.io/3wk8e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forgiveness and Perceived Social Support in Teenagers

Abstract: In this research, the aim is to investigate the relationship between forgiveness and perceived social support in teenagers in terms of various variables (gender, high school type, education level of parents, expressed relative communication and expressed family, friends, teacher support). The population of the research consists of high school students studying in Kocaeli province in 2019-2020 education year and the research sample consists of 422 students who are chosen with appropriate sampling method from fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…According to McCullough (2000), the proclivity to forgive others is associated with health, resulting in fewer stressful social interactions and encouraging social support. Some researchers believe that assessing and constructively minimizing life s negative experiences and offering social support will significantly improve one' s physical and mental health, particularly during adolescence (Bayın & Kaya, 2021). For instance, Bayın and Kaya's (2020) study found a favourable and significant correlation between forgiveness and adolescents' perceptions of social support.…”
Section: Introductionmentioning
confidence: 99%
“…According to McCullough (2000), the proclivity to forgive others is associated with health, resulting in fewer stressful social interactions and encouraging social support. Some researchers believe that assessing and constructively minimizing life s negative experiences and offering social support will significantly improve one' s physical and mental health, particularly during adolescence (Bayın & Kaya, 2021). For instance, Bayın and Kaya's (2020) study found a favourable and significant correlation between forgiveness and adolescents' perceptions of social support.…”
Section: Introductionmentioning
confidence: 99%